121k views
0 votes
Drag a reason to each box to complete the proof.Given:DF=EGProve:DE=FG

Drag a reason to each box to complete the proof.Given:DF=EGProve:DE=FG-example-1
User Samiyah
by
5.1k points

1 Answer

2 votes

Statement → Reasons

1. DF = EG → Given (because this is a given information in the proof).

4. DE + EF = EF + EG → Substitution Property of Equality

Statement 4 uses substitution property of equality that is based on Statement 1, 2, and 3. Since Statement 2 said DF = DE + EF then, we can substitute the DF in Statement 1 with DE + EF.

Similarly, Statement 3 says EG = EF + FG, then we can replace EG in Statement 1 with EF + FG.

Thus, making the statement 4 DE + EF = EF + FG.

5. DE = FG → Segment Congruence Postulate

Since Statement 4 has a common segment that is EF and both sides are equal, that just shows that what is being added to EF which are DE and FG are also equal too.

User Dan Murfitt
by
4.7k points